Optimization of protein extraction protocols for the identification of abundantly expressed proteins in the fruit, root and leaf of curculigo latifolio - Rastegari, Elham (2012)
Substantial achievements in proteomic techniques in the last decade have led to an increase in the application of proteomics to many fields, including plant sciences. Proteomics is a robust technology for the high-throughput investigation of proteins on a genome-wide scale. With the completion of genome sequencing projects and the improvement of analytical methods for protein identification, proteomics has now become a major tool for studying functional genomics. Despite the progress in proteomics research in animals, yeast and Escherichia coli, plant proteomics is still at infancy stages. Lemba, Curculigo latifolia, is an indigenous plant of Malaysia and is found mainly in swampy areas of tropical Asia and Australia. To date, there are no published reports of the proteome of this plant. This study focused on finding the best protein extraction protocols for specific tissues from this plant as judged by the optimal 2-DE patterns. This was an essential step that had to be performed before the identification of abundantly expressed proteins from the fruit, root and leaf could be attempted. Fruit, root and leaf tissues of Curculigo latifolia were individually subjected to 7 different published protocols (three different phenol based protocols, a TCA-acetone based protocol, a combination of phenol and TCA-acetone-based protocol, and a chloroformbased protocol) to determine the most efficient method for the specific tissue. Prior to the protein extraction of fruit, a novel pectolytic enzyme mix pretreatment was tested and was found to successfully reduce the amount of pectin which otherwise made protein extraction from that tissue nearly impossible. Chloroform, phenol and TCA-acetone-based protocols were found to be the most efficient methods for fruit, root and leaf respectively. The five most abundant spots for each tissue were excised from 2-DE gels and analyzed by MALDITOF/ TOF mass spectrometry, and identified by cross species comparisons employing available plant protein databases. Glutelin and RuBisCo were the most abundant proteins in the fruit and leaf respectively. In root, catalase and glyceraldehyde-3-phosphate were found to be the most abundant proteins.